Almacenamiento en tiempo real sobre Cloud Computing AWS y PostgreSQL de variables termodinámicas y eléctricas de un refrigerador doméstico 372 LRT F380G TMF conectado a un dispositivo IoT - ESP32 (2023)
This degree work is related to specific objective 1 of a Research Project VCTI2024-1 on the real performance of domestic refrigerators. It refers to the design and implementation of real-time data storage on Amazon Cloud Computing, using different AWS IoT Core Services. The IoT device used for data collection is a prototype developed in the VCTI Project 2019234 based on the ESP32 SoC that connects to the cloud to an instrumented 372 LRT F380G TMF domestic refrigerator. The configured AWS Services are fundamentally related to communication and access to AWS's own horizontally and vertically scalable Database. PostgreSQL is used to allow other applications to access the data, such as Matlab. The results of data recording and visualization are displayed in http applications in desktop and mobile versions respectively. Information corresponding to 31 variables is stored for a period of up to 12 months with sampling periods of 2.2 seconds.